PEMBUATAN PUPUK ORGANIK DAN APLIKASINYA PADA TANAMAN SAYURAN - Nurmi, Nurmi; Ilahude, Zulzain (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
The purpose of the service is to find out how to make organic fertilizer using rice husk raw materials and how to apply it to vegetable plants. The method used in this service is by holding counseling about the benefits of organic fertilizer, training in making rice husk organic fertilizer with an EM4 simulator, application of organic fertilizer as an organic planting medium in polybags, and program evaluation. The result of the dedication is in the form of transfer of research results on the technology for making organic fertilizer with an EM4 simulator, in this case the utilization of rice husk organic matter which is transferred from lecturers as researchers to farmers in the form of counseling and demonstrations. Partners take an active role in this service, especially in technical implementation in the field. The service program that was carried out was accepted by the farmers. Farmers are very optimistic that they can apply what they get in this service activity in the field, because this technology is very easy to apply. Fermented rice husk organic fertilizer is directly applied to several types of vegetable plants that have previously been planted in nurseries. Some vegetable plants grown in polybags are celery, chilies, tomatoes, kale, spinach and mustard greens. Plant growth in polybags that use organic growing media is quite good because of the improvement in soil properties played by the organic fertilizers given. Improvements in soil properties include improvements in physical, chemical and biological properties.